Proceedings of the 36th International Conference on Software Engineering 2014
DOI: 10.1145/2568225.2568297
|View full text |Cite
|
Sign up to set email alerts
|

SEEDS: a software engineer's energy-optimization decision support framework

Abstract: Reducing the energy usage of software is becoming more important in many environments, in particular, batterypowered mobile devices, embedded systems and data centers. Recent empirical studies indicate that software engineers can support the goal of reducing energy usage by making design and implementation decisions in ways that take into consideration how such decisions impact the energy usage of an application. However, the large number of possible choices and the lack of feedback and information available t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 144 publications
(95 citation statements)
references
References 50 publications
0
85
0
Order By: Relevance
“…The GA required approximately 3,500 fitness evaluations to find its best solution (the number of evaluations varied slightly between different evolutionary runs), while the exhaustive search at each variation point required only 105 evaluations. Although using the GA was therefore significantly slower than the approach used in similar work [9], the final result is also significantly better.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…The GA required approximately 3,500 fitness evaluations to find its best solution (the number of evaluations varied slightly between different evolutionary runs), while the exhaustive search at each variation point required only 105 evaluations. Although using the GA was therefore significantly slower than the approach used in similar work [9], the final result is also significantly better.…”
Section: Resultsmentioning
confidence: 87%
“…Thus, the results show that the substitutions improve both the energy consumption and the execution time of the class. We further compared the results of our technique to those obtained using an approach used in related work [9]-a separate exhaustive search at each variation point-and found that although the number of fitness evaluations increased using a GA, the performance of the final result was significantly improved. This shows that the variation points within code are not always independent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Li et al [80] formulate energy optimisation as the problem of finding the mobile device screen colour choices that minimise energy consumption, while maintaining colour contrast. Monotas et al [83] also define a search space for energy optimisation choices. They currently use an exhaustive search, but plan to extend to full SBSE for scalability to larger search spaces.…”
Section: Search Based Energy Testing (Sbet)mentioning
confidence: 99%